2022
DOI: 10.1155/2022/6073911
|View full text |Cite
|
Sign up to set email alerts
|

Blocking REDD1/TXNIP Complex Ameliorates HG-Induced Renal Tubular Epithelial Cell Apoptosis and EMT through Repressing Oxidative Stress

Abstract: Diabetic nephropathy (DN) has become the most common secondary kidney disease causing end-stage renal disease (ESRD). Nevertheless, the underlying mechanisms responsible for DN remain largely unknown. Regulated in development and DNA damage response 1 (REDD1) is a prooxidative molecule known to contribute to diabetes mellitus and its complications. However, it has not been previously examined whether and how REDD1 can further drive renal tubular epithelial cell (RTEC) apoptosis and epithelial-to-mesenchymal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Herein, we confirmed that the protein level of tight junction protein ZO-1 was decreased and fibroblast marker proteins including Vimentin, α-SMA, and Snail were increased in HGinduced HK-2 cells. These results were consistent with previously published work reported by Mu et al [20] and Gong et al [21]. Moreover, Wang et al [22] found that Shenkang injection could alleviate tubulopathy in the DN rat model by inhibiting EMT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Herein, we confirmed that the protein level of tight junction protein ZO-1 was decreased and fibroblast marker proteins including Vimentin, α-SMA, and Snail were increased in HGinduced HK-2 cells. These results were consistent with previously published work reported by Mu et al [20] and Gong et al [21]. Moreover, Wang et al [22] found that Shenkang injection could alleviate tubulopathy in the DN rat model by inhibiting EMT.…”
Section: Discussionsupporting
confidence: 93%
“…These results were consistent with previously published work reported by Mu et al . [ 20 ] and Gong et al . [ 21 ].…”
Section: Discussionmentioning
confidence: 99%